The type specimens of Trichomycterus alternatus (Eigenmann, 1917) and Trichomycterus zonatus (Eigenmann, 1918), with elements for future revisionary work (Teleostei: Siluriformes: Trichomycteridae) - Reis, Vinícius J. C.; de Pinna, Mário (Zootaxa, 2019)
The trichomycterid catfish species Trichomycterus alternatus (Eigenmann, 1917) and Trichomycterus zonatus (Eigenmann, 1918) are reportedly among the most pervasive species in mid- to high-elevation coastal streams of Southeastern Brazil. Despite their apparent abundance and ecological ubiquity, the applicability of their names is still uncertain. Examination of the type material of the two species reveals that part of the confusion stems from a mixing of species in the T. zonatus type series. Other issues relate to reports of character conditions in the respective species that do not actually correspond to the situation in their type specimens. Such situation triggered a long-lasting chain of taxonomic misinterpretations and erroneous identification protocols and traditions so that even the taxonomic distinctiveness of the two species is nebulous. That situation is disentangled in detail on the basis of new information on the holotypes and remaining type specimens of each species by classical and new (stereo triplet radiography) morphology analyses for data acquisition. Results show that the type specimens of T. alternatus and T. zonatus differ pronouncedly in several traits of internal and external morphology and represent markedly distinct taxa. The latter species does not correspond to most identifications in the literature and is, in fact, endemic to the region of its type locality. We also clarify and map the reported localities of the type material and offer comments on the validity of T. alternatus and T. zonatus, along with that of possibly related forms.